2023
DOI: 10.1021/acscatal.2c05303
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water on Zeolite-Catalyzed Dehydration of Polyalcohols and EVOH Polymer

Abstract: Selective dehydration of polyalcohols over zeolites containing Brønsted acids is a promising approach to purify and recycle multilayer polymer films consisting of non-polar polymers such as polyethylene and polar polymers like ethylene−vinyl alcohol copolymer. In addition, polar aprotic solvents can be utilized to improve the diffusion of polymer molecules to access the active sites in solid catalysts. Here, we reveal the positive role of water on dehydration of ethylene−vinyl alcohol polymer over a solid acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Water incorporation tends to not exhibit traditional competitive adsorption behavior. We have recently shown that some polar reactants (ethers) in the presence of strongly binding co-adsorbates that exhibit traditional Langmuir-Hinshelwood competitive adsorption behavior actually exhibit an improved ability to compete for active sites when water is co-fed . This was attributed to the delocalized nature of hydronium ion clusters that are created.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water incorporation tends to not exhibit traditional competitive adsorption behavior. We have recently shown that some polar reactants (ethers) in the presence of strongly binding co-adsorbates that exhibit traditional Langmuir-Hinshelwood competitive adsorption behavior actually exhibit an improved ability to compete for active sites when water is co-fed . This was attributed to the delocalized nature of hydronium ion clusters that are created.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that some polar reactants (ethers) in the presence of strongly binding co-adsorbates that exhibit traditional Langmuir-Hinshelwood competitive adsorption behavior actually exhibit an improved ability to compete for active sites when water is co-fed. 54 This was attributed to the delocalized nature of hydronium ion clusters that are created. Such modifications in rates of acid-catalyzed reactions are quite common with polar reactants where hydrogen bonding is prevalent, but reported enhancements in rates of C−C bond activation in hydrocarbons like cumene are rare.…”
Section: Kinetic Role Of Brønsted Acid Sites and Watermentioning
confidence: 99%
“…Utilizing confinement and/or sufficient hydrophilicity of the solvent system is thus postulated to facilitate the proton transfer in surface intermediates, which promotes ketone formation in the selective conversion of EVOH, as shown in our previous work. 52…”
Section: Resultsmentioning
confidence: 99%
“…Dehydration of 2,5-dimethyltetrahydrofuran has been less investigated than that of 2-methyltetrahydrofuran including the distribution of product isomers; however, several comparative studies showed that the reactivity of 2,5-dimethyltetrahydrofuran is surely higher than those of tetrahydrofuran and 2-methyltetrahydrofuran. 22,174 Very recently, Crossley et al reported dehydration of 2,5-hexanediol over the H-ZSM-5 catalyst at 523 K. 250 The product at short contact time was 2,5-dimethyltetrahydrofuran, and at longer contact time hexadienes were produced. Although it was not tested to fully convert 2,5-dimethyltetrahydrofuran with sufficiently long contact time, the selectivity to hexadienes ([hexadienes]/([all products] − [2,5-dimethyltetrahydrofuran])) was higher than 90%.…”
Section: Specific Productsmentioning
confidence: 99%